PENYELESAIAN TINDAK PIDANA PENCURIAN MELALUI MEDIASI PENAL (Studi Kasus di Polres Batu) - Ilham Fauzi Prakoso (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTThe Indonesian legal system recognizes the term criminal justice system as a system of law enforcement aimed at resolving and overcoming criminal cases that occur in society. The purpose of the criminal justice system is not only to process the settlement of criminal cases that are fast, inexpensive, and short but also to provide human rights protection, respect the principle of presumption of innocence and the process of punishment that provides a balance of law, defendants and victims. In dealing with these conditions, it takes the rules that underlie the settlement of criminal cases by promoting the principles of justice, expediency, and legal certainty. The Republic of Indonesia Police Agency is the main key in determining whether or not a criminal case can proceed into a criminal justice process, in this case issuing the Circular of the National Police Chief Number: SE / 8 / VII / 2018 dated July 27, 2018, concerning the Implementation of Restorative Justice Against Case Settlements Criminal. The author conducts research on how the mediation of the penal process carried out by the Batu Police in handling theft cases and whether the mediation process has brought about restorative justice. The rule can be used as a reference by investigators in conducting mediation outside the court by using the development of the principle of restorative justice, which means returning to normal before the crime took place.Key words: Settlement of criminal acts; Penal Mediation; Restorative Justice. ABSTRAKSistem hukum Indonesia mengenal istilah sistem peradilan pidana sebagai suatu sistem penegakan hukum yang bertujuan untuk menyelesaikan serta menanggulangi perkara pidana yang terjadi dalam masyarakat. Tujuan dari sistem peradilan pidana tidak hanya untuk memproses penyelesaian perkara pidana yang cepat, berbiaya murah dan singkat, akan tetapi juga memberikan perlindungan hak asasi manusia, menghormati asas praduga tak bersalah dan proses penghukuman yang memberikan jaminan keseimbangan terhadap hukum, terdakwa dan korban. Dalam menyiasati kondisi tersebut maka dibutuhkan aturan yang melandasi penyelesaian perkara pidana dengan mengedepankan asas keadilan, kemanfaatan dan kepastian hukum. Lembaga Kepolisian Republik Indonesia merupakan kunci utama penentuan dapat tidaknya suatu perkara tindak pidana dapat dilanjutkan ke dalam proses peradilan pidana, maka dalam hal ini mengeluarkan Surat Edaran Kapolri Nomor : SE/8/VII/2018 tanggal 27 Juli 2018 tentang Penerapan Keadilan Restoratif Terhadap Penyelesaian Perkara Pidana. Penulis melakukan penelitian tentang bagaimanakah proses mediasi penal yang dilakukan oleh Polres Batu dalam menangani perkara pencurian serta apakah proses mediasi tersebut telah mewujudkan keadilan restoratif. Aturan tersebut dapat digunakan sebagai acuan oleh penyidik dalam melakukan mediasi di luar pengadilan dengan menggunakan perkembangan dari prinsip keadilan restoratif, yang memiliki arti pengembalian keadaan seperti semula saat sebelum terjadi tindak pidana.Kata Kunci: Penyelesaian Tindak Pidana; Mediasi Penal; Keadilan Restoratif.